2000
DOI: 10.1046/j.1471-4159.2000.0740231.x
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Induces Cell Cytotoxicity and Oxidative Stress and Increases β‐Amyloid Secretion and Tau Phosphorylation in SHSY5Y Neuroblastoma Cells

Abstract: Abstract:Concentrations of heavy metals, including mercury, have been shown to be altered in the brain and body fluids of Alzheimer's disease (AD) patients. To explore potential pathophysiological mechanisms we used an in vitro model system (SHSY5Y neuroblastoma cells) and investigated the effects of inorganic mercury (HgCl 2 ) on oxidative stress, cell cytotoxicity, ␤-amyloid production, and tau phosphorylation. We demonstrated that exposure of cells to 50 g/L (180 nM) HgCl 2 for 30 min induces a 30% reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
1
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(130 citation statements)
references
References 31 publications
1
121
1
7
Order By: Relevance
“…In vitro studies produced the following results: Mercury interferes with polymerization of microtubules [122,123], increases secretion of both 1-40 and 1-42 forms of Aβ and promotes hyperphosphorylation of tau protein [9,[124][125][126][127], changes mitochondrial structure inducing a stress-response in astrocytes [128], and interferes with cell-maturation [129] or other aspects of cell functioning, such as DNA repair, glutathione level, or linkage and structure of microtubules [119,130,131]. Mercury disturbs the interaction between tubulin and GTP [132], and the chelator DMSA can reverse this process [133], while amalgam exposure is toxic for nerve cells in vitro [134].…”
Section: Experimental Animal and In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies produced the following results: Mercury interferes with polymerization of microtubules [122,123], increases secretion of both 1-40 and 1-42 forms of Aβ and promotes hyperphosphorylation of tau protein [9,[124][125][126][127], changes mitochondrial structure inducing a stress-response in astrocytes [128], and interferes with cell-maturation [129] or other aspects of cell functioning, such as DNA repair, glutathione level, or linkage and structure of microtubules [119,130,131]. Mercury disturbs the interaction between tubulin and GTP [132], and the chelator DMSA can reverse this process [133], while amalgam exposure is toxic for nerve cells in vitro [134].…”
Section: Experimental Animal and In Vitro Studiesmentioning
confidence: 99%
“…Very low levels (180 nM) of Hg ++ decrease glutathione levels (GSH) and increase oxidative and nitrosative stress, which may lead to cytotoxicity [9]. The extraordinarily high affinity of Hg ++ for selenium, and selenoproteins (dissociation constant = 10 −45 ) [10] can disrupt cellular redox balance [11,12], especially in the brain, which uniquely depends upon selenoenzymes for antioxidant protection and hence selenium [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Extended deprivation of melatonin can lead to elevated levels of oxidative damage [37]. This agent can reduce the extent of injury to the CNS caused by a wide range of neurotoxicants including iron-induced necrosis [25], mercury [30], kainate [28], cyanide [52] and paraquat [29]. Melatonin levels decrease with age [33].…”
Section: Introductionmentioning
confidence: 99%
“…NFTs are one of the main pathological signatures of Alzheimer's disease and their presence positively correlates with the severity of dementia in this condition [40]. Studies from various laboratories have shown that oxidative stress results in the hyperphosphorylation of Tau in both animal and cultured neuronal cell models [41][42][43]. It is noteworthy in this regard that the present study has indicated that both ()Sch B and EGCG can suppress the hyperphosphorylation of Tau through the reduction of cellular oxidative stress levels, as indicated by a reduction in GSH depletion under A-challenged conditions.…”
Section: Discussionmentioning
confidence: 99%